Sedimentary provenance supports a mid-paleozoic tectonic connection between the Junggar and Altai terranes in central Asia - Di Li; Yigui Han; Guochun Zhao; Mei-Fu Zhou; Dengfa He; Shuoqin Hou; Yu Zhen; Dan Fan; Hao Yang (Scientific Reports, 2024)
Abstract The provenance of Precambrian detritus in the Junggar and Altai terranes provides crucial constraints on the peri-Siberian accretionary tectonic evolution in the middle Paleozoic. The Precambrian detrital zircons have no coeval magmatic equivalents in the Junggar terrane but show U–Pb age spectra and εHf(t) values comparable to those in the Altai terrane. The correlations suggest that the old detrital materials in the Junggar and Altai terranes were most likely derived from the Siberia craton and adjacent Tuva-Mongolian microcontinent. Paleozoic zircons in the Junggar terrane display a εHf(t) pattern from large spread to dominantly positive values at ca. 420–410 Ma. Such an abrupt change points to an accretionary tectonic transition from an advancing to retreating mode during mid-Paleozoic time, synchronous with similar tectonic switch occurring in the Altai terrane. Taking into account the temporal and spatial relations in sedimentation, tectonism and arc magmatism, we propose that the Junggar terrane had once collided onto the peri-Siberian Altai terrane to receive abundant old detritus from the Siberian continent in the Silurian–early Devonian. They were subsequently separated at ca. 420–410 Ma, possibly due to the slab rollback of the subducting Paleo-Asian Ocean (PAO) plate. These results constrain an Early Paleozoic tectono-paleogeographic boundary of the CAOB along the North Tianshan–Solonker suture zone, and also imply a long-lived PAO subduction was responsible for the Neoproterozoic to Paleozoic accretionary orogenesis at the margins of southern Siberia, eastern Kazakhstan, and northern Gondwana.